Improvement of electrical conductivity of PEMA film by incorporating EMITFSI and carbon based nanofiller - Zain, N.F.; Rozali, Shaifulazuar; Mohamad, Mahazani; Tengku Mohmed Noor Izam, Tengku Faiz; Sabri, Mohd Faizul Mohd; Mohamed, Nor Sabirin; Said, Suhana Mohd; Salleh, Faiz (Elsevier, 2020)
The electrical conductivity of dual inclusion of 1-ethyl-3-methyl imidazolium bis(trifluorosulfonyl) imide ionic liquid and three allotropes of carbon based nanofillers (multiwalled carbon nanotube, graphene and graphite) in poly (ethyl methacrylate) films with thickness ranging from 100 to 250 μm has been investigated in the temperature range of 300–380 K. It is found that the electrical conductivity of film with 0.5 wt % multiwalled carbon nanotube has the highest ambient electrical conductivity of 4.9 × 10−6 Scm−1 which is five order of magnitude higher than pure poly (ethyl methacrylate) film. Moreover, the stability of the highest electrical conductivity is also found to be significantly improved for a longer period. From the investigated physicochemical properties, these improvements are likely can be explained by the aggregation of multiwalled carbon nanotubes, the increase in electronic transport and the reduction in glass transition temperature which likely effect its ionic mobility. Consequently, these enhancements may lead to a promising improvement of its electrical properties for a stable near room temperature application. © 2019 Elsevier B.V.